Real time magnetic control of the snowflake plasma configuration in the TCV tokamak. (14th October 2019) - Anand, H.; Coda, S.; Felici, F.; Galperti, C.; Moret, J.-M.; Labit, B.; Reimerdes, H.; Maurizio, R.
Abstract: The novel plasma position and shape controller of the TCV tokamak aids in the precise control of complex configurations such as snowflake (SF) divertors. The ability of the controller design to simultaneously control the position, shape, divertor leg and X-points is extended to various SF plasma configurations. The unique feature of ordering the controlled variables from the most easily to the least easily controlled, while respecting the hardware limits on the poloidal-field coil currents, is exploited in particular to provide reliable control of SF equilibria with closely spaced X-points, approaching the exact snowflake. The off-line optimisation of the control parameters and their experimental implementation on snowflake plasma configuration is reported. The performance of the new controller is compared with the legacy TCV analogue controller for a SF plasma discharge. The new controller is successful in providing a marked improvement over the legacy TCV controller with respect to, the main parameter of interest for this study.